EFEKTIVITAS PERATURAN DIRJEN BIMAS ISLAM TENTANG KURSUS CALON PENGANTIN UNTUK MEMINIMALISIR TINGGINYA ANGKA KDRT DI KOTA TANJUNG BALAI - Adi Syahputra Sirait (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2019)
In Islam protecting for the household is an obligation. An it’s become the foundation of Directur General for Islamic Guidance about regulations on brides course with the destination for each people in the family have knowledge and understanding on the concept of good family. Therefore, differences and miss understanding often be sources of separation and devore, since 2010 – 2017 the divorce increase so significantly especially in Tanjung Balai. This study use social legal research, it’s mean to see how the effectivieness of the bride courses in Tanjung Balai reducing the divorces and domestic violence an how should the effectiveness of the regulation for the brides. So that the divorce rate can be minimized in accordance with islamic taught an the National Law, and also the domestic violence.